Self‐Healing and Injectable Hydrogel for Matching Skin Flap Regeneration - Mao Xiyuan; Cheng Ruoyu; Zhang Hongbo; Bae Jinhong; Cheng Liying; Zhang Lu; Deng Lianfu; Cui Wenguo; Zhang Yuguang; Santos Hélder A; Sun Xiaoming (Wiley Online Library, 2022)
The fabrication of highly biocompatible hydrogels with multiple unique healing abilities for the whole healing process, for example, multifunctional hydrogels with injectable, degradation, antibacterial, antihypoxic, and wound healing–promoting properties that match the dynamic healing process of skin flap regeneration, is currently a research challenge. Here, a multifunctional and dynamic coordinative polyethylene glycol (PEG) hydrogel with mangiferin liposomes (MF-Lip@PEG) is developed for clinical applications through Ag–S coordination of four-arm-PEG-SH and Ag+. Compared to MF-PEG, MF-Lip@PEG exhibits self-healing properties, lower swelling percentages, and a longer endurance period. Moreover, the hydrogel exhibits excellent drug dispersibility and release characteristics for slow and persistent drug delivery. In vitro studies show that the hydrogel is biocompatible and nontoxic to cells, and exerts an outstanding neovascularization-promoting effect. The MF-Lip@PEG also exhibits a strong cytoprotective effect against hypoxia-induced apoptosis through regulation of the Bax/Bcl-2/caspase-3 pathway. In a random skin flap animal model, the MF-Lip@PEG is injectable and convenient to deliver into the skin flap, providing excellent anti-inflammation, anti-infection, and proneovascularization effects and significantly reducing the skin flap necrosis rate. In general, the MF-Lip@PEG possesses outstanding multifunctionality for the dynamic healing process of skin flap regeneration.